2021
DOI: 10.1101/2021.05.20.444938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ApoE4 disrupts interaction of sortilin with fatty acid-binding protein 7 essential to promote lipid signaling

Abstract: Sortilin is a receptor for neuronal uptake of apolipoprotein E. Sortilin-dependent uptake of lipidated apoE promotes conversion of polyunsaturated fatty acids (PUFA) into neuromodulators that induce anti-inflammatory gene expression in the brain. This neuroprotective pathway works with apoE3 but is lost with apoE4, the main risk factor for Alzheimer disease (AD). Here, we elucidated steps in cellular handling of lipids through sortilin, and why they are disrupted by apoE4. Combining unbiased proteome screens w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…These observations were in marked contrast to SorLA deficient mice that exhibited no accumulation of ApoE, supporting the model of Sortilin's direct effect on ApoE and Aβ turnover [93]. Most recently, the same research group studied the relevance of the Sortilin-mediated uptake of ApoE for brain lipid metabolism [243,244]. They found that Sortilin is required to accumulate and facilitate the metabolism of polyunsaturated fatty acid into endocannabinoids; lipids with potent anti-inflammatory and neuroprotective functions.…”
Section: Sortilin Interactions In Amyloidogenic Cascadementioning
confidence: 67%
See 1 more Smart Citation
“…These observations were in marked contrast to SorLA deficient mice that exhibited no accumulation of ApoE, supporting the model of Sortilin's direct effect on ApoE and Aβ turnover [93]. Most recently, the same research group studied the relevance of the Sortilin-mediated uptake of ApoE for brain lipid metabolism [243,244]. They found that Sortilin is required to accumulate and facilitate the metabolism of polyunsaturated fatty acid into endocannabinoids; lipids with potent anti-inflammatory and neuroprotective functions.…”
Section: Sortilin Interactions In Amyloidogenic Cascadementioning
confidence: 67%
“…The combined findings are schematized in (Fig. 5, BOX D) and suggest a protective role of Sortilin in AD by lowering Aβ levels, reducing production of neuroinflammatory cytokines [244,245], stimulating synapse function, and sustaining neuron viability.…”
Section: Sortilin Interactions In Amyloidogenic Cascadementioning
confidence: 95%
“…The authors explain this apparent paradox by ApoE4 being unable to uncouple from sortilin in the endosomal compartment, which disrupts recycling and re-exposure of the receptor at the plasma membrane. The combined findings suggest a protective role of sortilin in AD by lowering A levels, reducing production of neuroinflammatory cytokines [182,183], stimulating synapse function, and sustaining neuron viability (Figure 5…”
Section: O Sortilin's Interactions In Amyloidogenic Cascadementioning
confidence: 95%
“…However, the absence of sortilin significantly attenuated the uptake of ApoE-A complexes, demonstrating that impaired ApoE clearence by sortilin causes accumulation of Aβ in the brain [92]. Most recently, the same research group went on to study the relevance of the sortilin-mediated uptake of ApoE for brain lipid metabolism [181,182]. They found that sortilin is required to accumulate and facilitate the metabolism of polyunsaturated fatty acid into endocannabinoids; lipids with potent anti-inflammatory and neuroprotective functions.…”
Section: O Sortilin's Interactions In Amyloidogenic Cascadementioning
confidence: 99%